Anatomy of Administrative Immigration Oversight Blind Spots: A Socio-Legal Study on the Paralysis of Early Warning Systems in Makassar - Pawallangi, Andi Zhafwan Iqrar; Sapiddin, Andi Syahwiah A.; Latif, Birkah; Rastiawaty, Rastiawaty; Rivanie, Syarif Saddam (CV. Social Politic Genius (SIGn), 2025)
This in-depth research investigates the anatomy of blind spots within post-admission administrative oversight mechanisms for foreign nationals at the Makassar Immigration Checkpoint and elucidates the causal determinants that trigger the paralysis of early warning systems. The urgency of this study stems from the high rate of overstays, which reflects structural dysfunction in immigration governance within the primary transit territory of Eastern Indonesia. Employing an empirical legal research method with a socio-legal approach, primary data are triangulated through in-depth interviews, field observations, and statistical analysis of violations. The research results uncover a critical discrepancy between digital data registration at the port of entry and continuous field surveillance, resulting in the state losing control over the dynamic nomadic movements of foreign legal subjects. Juridically, this systemic paralysis constitutes a violation of the Principle of Carefulness, triggered by a chronic human resource deficit in the intelligence unit and the nullity of regulatorily mandated cross-sectoral information technology interoperability. Consequently, law enforcement tends to be constrained by reactive patterns and dependent on repressive deportation measures during the repressive phase. This study concludes that a paradigm reorientation towards risk-based surveillance, the transformation of apparatuses into administrative data analysts, and the reinforcement of the legal framework mandating real-time inter-agency data integration are necessary. These policy implications constitute absolute prerequisites for restoring legal authority and guaranteeing state sovereignty through proactive prevention mechanisms in the preventive phase.